THE EFFECT OF MONETARY POLICY AND FISCAL POLICY ON INFLATION IN INDONESIA - Cica Clara Br Sitepu; Syahrian Ramadhan; Gilang Panca Putra Ginting; Rizki Nugraha; Monika Andrasari (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Inflation has been one of the biggest challenges for Indonesia's economic development. A stable and manageable inflation rate is important to create a healthy economic environment, increase people's purchasing power, and promote sustainable economic growth. In an effort to control inflation, the Indonesian government uses various policy instruments, including monetary policy and fiscal policy. The type of research used is a quantitative approach with secondary data from 1993-2022 obtained from the website of Bank Indonesia, Ministry of Finance, Central Bureau of Statistics, and several other library materials that researchers read. The data was then processed using Eviews 12 software and analyzed using the Autoregressive Distributed Lag (ARDL) analysis technique. The results showed that the money supply variable has a significant positive effect in the long term while in the short term the money supply variable has a significant positive effect on lag 0 and a significant negative effect on lag 2 on inflation in Indonesia. The interest rate variable has a positive significant effect in the long run while in the short term the interest rate variable has a positive significant effect on lag 0 and negative significant on lag 1 and 2 on inflation in Indonesia. The tax revenue variable has a positive significant effect in the long run while in the short term the tax revenue variable has a positive significant effect on lag 0, 1 and 2 on inflation in Indonesia. The government spending variable has a significant negative effect in the long run while in the short term the government spending variable has a significant negative effect on lag 0 and a significant positive effect on lags 1, 2 and 3 on inflation in Indonesia.